Addition - Midthun, Joseph; Hiti, Samuel; World Book, Inc. (Chicago World Book, a Scott Fetzer Company, 2013)
"A graphic nonfiction volume that introduces critical basic addition concepts"--
What is addition? -- Counting on -- Adding with insects -- Doubles -- Making friendly numbers -- Fish in the sea -- Matching and counting up -- Addition all around.
Includes bibliographical referencesa (page 32) and index.
106421
Keywords: Addition -- Comic books, strips, etc; Graphic novels; Mathematics; Children's nonfiction; Juvenile works